Mortality in international professional football (soccer): a descriptive study - Gouttebarge, V.; Ooms, W.; Tummers, T.; Inklaar, H. (The Journal of Sports Medicine and Physical Fitness, 2016)
The objective of this study was to describe the characteristics of mortalities from 2007 to 2013 in active (during career) and recently retired (post career) professional footballers. An observational prospective study was conducted. From 2007, the World Footballers' Union (FIFPro) and its related national footballers' unions (more than 70 countries distributed across all continents) collected descriptive data (football-related, cause, etc.) on mortality of active (during career) and recently retired (postcareer before reaching 45 years of age) professional footballers by means of several official sources. A total of 214 deaths were recorded among active and recently retired professional footballers, leading to an overall mortality rate of 0.47 per 1000 footballers per year. Of the 214 deaths, 183 were recorded among active players and 31 among recently retired players. Among the active players, 17% of the fatalities were related to football participation. Disease was the leading cause of death among professional footballers (55%), of which up to 33% accounted for suspected cardiac pathology. Accidents accounted for 25% of the overall deaths, and suicide for 11%. From 2007 to 2013, 214 deaths were recorded among active (during career) and recently retired (post career) professional footballers. Leading cause of death was disease (55%), one third of which were accounted for by suspected cardiac pathology, while accidents accounted for 25% of all deaths, and suicide for 11%. Attention to the predictive validity and application of heart-related precompetition medical assessment should be given, and mental health support should be developed and implemented both during and after a professional football career to prevent potential suicidal behaviors.